Effect of heat treatment on cyclic fatigue resistance, thermal behavior and microstructures of K3 NiTi rotary instruments. (November 2013) - Chang, Seok Woo; Kim, Yu-Chan; Chang, Hyejung; Jee, Kwang-Koo; Zhu, Qiang; Safavi, Kamran; Shon, Won-Jun; Bae, Kwang-Shik; Spangberg, Larz Sw; Kum, Kee-Yeon
Abstract Objective. The aim of this study was to investigate the effect of heat treatment on the cyclic fatigue resistance, thermal behavior and microstructural changes of K3 NiTi rotary instruments. Materials and methods. Twelve control (as-received) and 12 experimental (heat-treated) K3 NiTi rotary instruments were compared in this study. Those experimental K3 instruments were heated in a furnace for 30 min at 450°C and then quenched in water. The cyclic fatigue resistance was measured with a fatigue tester. The thermal characteristic and the microstructures of both instruments were investigated by differential scanning calorimetry (DSC) and transmission electron microscopy (TEM), respectively. Results. There was a significant increase in the cyclic fatigue resistance between the heat-treated instruments and the as-received instruments (T-test, p < 0.05). DSC showed that the as-received and heat-treated samples were different, with an increased Af (austenite-finish temperature) for the latter. TEM analysis revealed that both as-received and heat-treated instruments were composed mainly of an austenite phase. However, the heat-treated samples had an increased appearance of larger grains, twinning martensite, TiO2 surface layer and a Ni-rich inner layer. Conclusions. Heat treatment increased the cyclic fatigue resistance of NiTi files and changed the thermal behavior of the instruments without marked changes in the constituting phases of NiTi alloy.